Implementasi Kebijakan Penyediaan Beras Bagi Aparatur Sipil Negara: Perspektif Model Advocacy Coalition Framework (ACF): (Studi pada Peraturan Bupati Nomor 64 Tahun 2021, Pemerintah Kabupaten Sumenep) - Bisri, Mashur Hasan; Dinata, Candra; Sarmini, Sarmini; Gamaputra, Gading; Pradana, Galih Wahyu (Journal of Indonesian Rural and Regional Government, 2025)
Implementation of policy Number 64 of 2021 concerning the provision of rice for the State Civil Apparatus (ASN) as a form of government favoritism to empower farmers by buying local agricultural products due to food price instability, economically affecting ASN's food needs so that ASN performance productivity decreases. This research study aims to explain the implementation of the rice provision policy for ASN based on Regent Regulation Number 64 of 2021 in Sumenep district, in the perspective of the Advocacy Coalition Framework (ACF) Model. The research method used is qualitative research. The results of this study are first, individual actors influencing the policy-making process of providing rice for ASN provide input in formulating strategies or actions taken to achieve the desired goals and objectives of the rice provision policy for ASN. However, the implementation of this policy considers aspects of sustainability and is not only temporary in order to provide sustainable benefits for ASN in the Sumenep district government. second, group actors have different roles depending on the stage of the ongoing policy cycle. group actors can assist in identifying problems or issues raised in the rice provision policy process for ASN.